Digital Finance Strengthening Model to Support Sustainable Supply Chains for MSMEs in Sei Semayang Village - Syaula, Maya; Pratama, Siswa; Ayu Lestari, Dinda (Yayasan Multidimensi Kreatif, 2025)
This research aims to explore the role of digital finance in supporting sustainable supply chains in Micro, Small, and Medium Enterprises (MSMEs) in Sei Semayang Village. The approach used is descriptive qualitative with data collection through in-depth interviews, field observations, and documentation of MSME transactions. The research informants consist of MSME actors, suppliers, as well as financial and fintech institutions related to MSME operational activities. The results of the study show that digital finance, such as e-wallets, mobile banking, QRIS, and fintech platforms, is able to improve the efficiency of financial management, accelerate cash flow, and smooth the supply chain of MSMEs. The integration of the digital financial system with raw material procurement, production, and distribution allows the flow of capital and goods to run more stable and transparent. However, the adoption of digital finance is still limited due to low digital and financial literacy, limited infrastructure, and dependence on traditional suppliers. This research formulates a model for strengthening digital finance which includes digital literacy training, integration of financial systems with supply chains, collaboration with fintechs and suppliers, monitoring and evaluation of transactions, and support of technological infrastructure. This model is expected to increase the efficiency, transparency, and sustainability of the MSME supply chain in Sei Semayang Village. The research findings provide practical contributions for MSME actors, financial institutions, fintech, and local governments in supporting the development of digital finance-based MSMEs.